Two-layer two-phase material point method simulation of granular landslides and generated tsunami waves - Zhao, Kai-Li; Qiu, Liu-Chao; Liu, Yi (Physics of fluids (1994), 2022)
Numerical modeling of the entire process of tsunamis generation by granular landslides is very difficult and challenging as it involves the soil–water interaction, large deformation of soil, and the fluidization and sedimentation of sand. In this study, a computational model based on the two-layer two-phase material point method (MPM) is developed to simulate granular-landslide-generated tsunamis, wherein the soil–water interaction, large deformation of soil, and fluidization and sedimentation of sand are well modeled. The soil behavior is described using a Mohr–Coulomb model with a non-associated flow rule, while the water is considered as weakly compressible. Furthermore, three different benchmark problems are simulated. All computed results well agree with the corresponding analytical solution and laboratory test data, verifying the effectiveness of the proposed two-layer two-phase MPM for modeling the subaerial and submerged granular-landslide-generated tsunamis. Additionally, the influence of different soil material parameters on the water wave generated by the subaerial granular landslide is investigated.